Regarding bill payment for supply installation, testing and commissioning of 415V, 50Hz, TPN+PE sandwich copper type tested Busbar Trunking System at BRACU new campus project - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the payment of supply, installation, testing and commissioning of Busbar Trunking System (BBT) for BRACU new campus project.